2013
DOI: 10.7567/jjap.52.08jk04
|View full text |Cite
|
Sign up to set email alerts
|

Impact of AlN Spacer on Metal–Semiconductor–Metal Pt–InAlGaN/GaN Heterostructures for Ultraviolet Detection

Abstract: We report on metal-semiconductor-metal (MSM) photodetectors (PDs) fabricated on InAlGaN/GaN two-dimensional electron gas (2DEG) heterostructures. Electrical and photodetection properties were compared in two structures with and without an AlN spacer between the barrier (InAlGaN) and the GaN. The presence of the spacer hugely reduces the leakage current, allowing biasing at higher voltages. In photodetection, gain is obtained in both structures at a high bias. The photocurrent transient behavior revealed a fast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 18 publications
(20 reference statements)
0
8
0
Order By: Relevance
“…This potential differences occurred owing to the polarization field (Keller et al, 2002) as shown in equation ( 1) (Lenka and Panda, 2011) where DE c 2 and DE c 1 are the effective conduction band offsets between the interfaces in Structure 2 and the Structure 1, respectively; N 2D is the sheet carrier concentration of Structure 2, « 2 is dielectric constant, s 2 is the polarization induced charge at the heterointerfaces of Structure 2, and t b is the thickness of barrier. The effective Schottky barrier of the quaternary structure will also increase with the presence of AlN spacer barrier, which eventually reduces the device leakage (Brazzini et al, 2013):…”
Section: Device Spacer Layermentioning
confidence: 99%
See 1 more Smart Citation
“…This potential differences occurred owing to the polarization field (Keller et al, 2002) as shown in equation ( 1) (Lenka and Panda, 2011) where DE c 2 and DE c 1 are the effective conduction band offsets between the interfaces in Structure 2 and the Structure 1, respectively; N 2D is the sheet carrier concentration of Structure 2, « 2 is dielectric constant, s 2 is the polarization induced charge at the heterointerfaces of Structure 2, and t b is the thickness of barrier. The effective Schottky barrier of the quaternary structure will also increase with the presence of AlN spacer barrier, which eventually reduces the device leakage (Brazzini et al, 2013):…”
Section: Device Spacer Layermentioning
confidence: 99%
“…Apparently, there is a limiting factor to the increment of Al mole fraction in Al x Ga 1-x N barrier where the Al percentage can only be increased up to 40 per cent to improve the 2DEG concentration and mobility (Arulkumaran et al, 2003). Earlier works have shown that by altering the device's structure such as modifying barrier doping (Firoz and Chauhan, 2011), stepgrading the structure layers (Yu et al, 2014;Das et al, 2014), as well as inserting interlayers in between the heterointerfaces (Roy et al, 2015;Shrestha et al, 2013;Brazzini et al, 2013), one can adjust the 2DEG concentration and also the device's mobility in the channel layer significantly. Besides that, design optimization in terms of physical dimensions is also vital in minimizing feature sizing without degrading their performances especially in switching speed and power consumptions (Binder et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…quantum efficiency = 1). As previously seen in the past, 123 this means that gain is present in the structure. The mechanism for the gain is not well understood yet.…”
Section: Chapter 10 Photodetectorsmentioning
confidence: 55%
“…118,119 In fact, photodetector based on HEMT structures has been succesfully fabricated and tested. [118][119][120][121][122][123] CHAPTER…”
Section: Inal(ga)nmentioning
confidence: 99%
See 1 more Smart Citation